Membangun Aplikasi Sistem Informasi untuk Meningkatkan Efisiensi dan Transparansi pada Lembaga Amil Zakat Nasional: Wahdah Inspirasi Zakat Kalimantan Timur Menggunakan Macro Microsoft Excel - Dhanny, Omar; Patabang, Lewi; Amirudin; Gunawan, Candra; Kusuma, Angga; Sailawati (Politeknik Negeri Samarinda, 2024)
Recording transactions, both receipt and distribution, to zakat institutions is an important activity that must be carried out by Zakat Institutions, including Wahdah Inspirasi Zakat Kaltim. With this recording, all transactions can be accounted for in reports. Designing database and transaction records for zakat institutions is a very important thing for these institutions to have. Building an application information system for this zakat institution aims to help carry out activities in recording and reporting its finances by creating an accounting design based on Macro Microsoft Excel. Building an information system is the process of designing a system for recording, processing and reporting information that suits the needs and goals of users. The method used is conducting interviews and observations as the basis for making the application. The result of this activity is an Information System Application that is tailored to the zakat institution. The final stage of the process is implementation for operators by providing training